2021
DOI: 10.26434/chemrxiv-2021-ldzzz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Silico Modeling and Scoring of PROTAC-Mediated Ternary Complex Poses

Abstract: Proteolysis targeting chimeras (PROTACs) are bifunctional molecules that can induce the ubiquitination of targeted proteins via the formation of ternary complexes between an E3 ubiquitin ligase and a target protein. The poly-ubiquitinated target protein will be escorted to the proteasome for degradation. Rational design of PROTACs require knowledge of an accurate configuration of the PROTAC induced ternary complex. This study demonstrates that native ternary poses can be distinguished by scoring candidate pose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…The MD refinement procedure is similar to our previous method used for PROTAC modeling. 32 From these results, we observed that the carbamate carbonyl oxygen of 6F forms a H-bond with neighboring Histidine 353. The phenyl, 2-methyl, 3-alkyne group, and Boc t-butyl all form hydrophobic contacts with the protein.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…The MD refinement procedure is similar to our previous method used for PROTAC modeling. 32 From these results, we observed that the carbamate carbonyl oxygen of 6F forms a H-bond with neighboring Histidine 353. The phenyl, 2-methyl, 3-alkyne group, and Boc t-butyl all form hydrophobic contacts with the protein.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…Sophisticated enhanced sampling techniques and distributed computing are needed to sample an ensemble of low-energy conformations that are consistent with experimental data. 40 Due to the difficulties in modeling the ternary complex, direct calculation of the binding cooperativities was not attempted until two recent studies 41,42 that explored the molecular mechanics with the generalized Born and surface area continuum solvation (MM/GBSA).…”
Section: ■ Introductionmentioning
confidence: 99%
“…This deficiency has been addressed in the next generation of methods which begin to appear in the 2022 literature. Liao, Junzhuo, et al (2022) [3] and Li, Wenqing, et al (2022) [4] have reported methods that use molecular mechanics combined with the generalized Born and surface area continuum solvation (MMGBSA) and Molecular Mechanics Poisson-Boltzmann Surface Area (MMPBSA) calculated ΔGs to relatively rank PROTAC candidates and achieved a good correlation (R 2 > 0.9) with ranking based on experimentally measured quantities from PROTAC assays. This we call as the third generation of methods.…”
Section: Introductionmentioning
confidence: 99%